Sistem Pendukung Keputusan Metode Electre pada Bauran pemasaran (7P) dalam Memulai Usaha Jasa Center - Sutrisno Sutrisno; Agus Darmawan; Fanisya Alva Mustika (Universitas Indraprasta PGRI Jakarta, 2017)
When starting a business, many prospective entrepreneurs find the capital an obstacle because they thinkthat they do not have enough capital. In fact, to run a business, the most important capital is a non-material capital such as marketing management science with marketing mix theories. The marketing tool is known as